Effect of Foundation Nonlinearity on Seismic Response of an Existing Arch Dam - Parisa Parsa Mahmoudi; Hasan Mirzabozorg; Mehdi Varmazyari; Seyyed Meisam Aghajanzadeh (Salehan Institute of Higher Education, 2016)
In the present paper, the effect of foundation nonlinearity on the seismic response of an existing arch dam is investigated. Luzzone arch dam in Switzerland is selected as a case study. The foundation nonlinearity is originated from opening/slipping of joints between a potential wedge at the left abutment and remaining foundation. Reservoir's water is assumed compressible and the coupled system is solved simultaneously. Also, the foundationis assumed massed medium via viscous boundary on the far-end truncated boundary. Two cases are considered in the analyses; the system applying reservoir pressure on the foundation; the system with no reservoir pressure applied on the foundation. The results reveal that the ignoringreservoir pressure on the foundation overestimates the response of the dam body. Finally, based on the conducted analyses, considering foundation nonlinearity has no significant effect on the results in the considered case due to special design of the body shape.